2000
DOI: 10.1093/glycob/10.5.493
|View full text |Cite
|
Sign up to set email alerts
|

The  - and  -subunits are required for expression of catalytic activity in the hetero-dimeric glucosidase II complex from human liver

Abstract: The alpha- and beta-subunits of the hetero-dimeric glucosidase II complex from human liver were cloned and expressed in COS-1 cells. The 4106 bp full-length cDNA for the alpha-subunit contained a 2835 bp ORF encoding a 107 kDa polypeptide. The 2095 bp cDNA for the beta-subunit encodes a approximately 60 kDa protein in a continuous 1605 bp ORF. The alpha- and beta-subunits each contain two potential Asn-Xaa-Thr/Ser acceptor sites, with only one site in the alpha-subunit (Asn97) being glycosylated. Additional la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…Again, this sequence was typical of a type II membrane protein, having a predicted 2-amino-acid cytosolic tail and a 20-amino-acid transmembrane region. The glycosyl hydrolase family 31 members contain a short peptide segment of conserved amino acids (DGXWIDMNEXSXF), including a conserved Asp residue that is thought to be involved in catalysis (25,32,33,38,72). A similar peptide sequence ( 487 IHLWNDMNEPSVF 499 ) is present in CaRot2, indicating that this protein also belongs to the same protein family.…”
Section: Resultsmentioning
confidence: 99%
“…Again, this sequence was typical of a type II membrane protein, having a predicted 2-amino-acid cytosolic tail and a 20-amino-acid transmembrane region. The glycosyl hydrolase family 31 members contain a short peptide segment of conserved amino acids (DGXWIDMNEXSXF), including a conserved Asp residue that is thought to be involved in catalysis (25,32,33,38,72). A similar peptide sequence ( 487 IHLWNDMNEPSVF 499 ) is present in CaRot2, indicating that this protein also belongs to the same protein family.…”
Section: Resultsmentioning
confidence: 99%
“…Gtb1p is a soluble glycoprotein localized in the ER lumen, where it interacts with Gls2p in a manner reminiscent of the heterodimeric structure of mammalian Glucosidase II (11,12). Interestingly, neither Gls2p nor Gtb1p contain any recognizable ER retention motifs, and yet both are evidently ER-localized.…”
Section: Discussionmentioning
confidence: 99%
“…Gls2p Localization Is Unaffected in ⌬gtb1 Cells-It has been suggested that GII␤ may contribute to the stability and/or ER retention of GII␣ in mammalian cells (11,12). We therefore further examined the expression of Gls2p in ⌬gtb1 cells.…”
Section: Gtb1 Encodes the Yeast Homologue Of Gii␤-there Is A Singlementioning
confidence: 99%
“…Since then, glucosidase II has been partially or completely purified from a wide variety of both lower and higher eukaryotic organisms (2,6,7,11,20,38,78,80,88). Following some initial controversy, it is now generally accepted that the protein is a rather asymmetric nonglobular heterodimer consisting of a catalytic alpha subunit with a molecular mass of about 110 kDa (GII␣) and a beta subunit with a molecular mass of 60 kDa (GII␤) (6,15,65,85,86,88).…”
mentioning
confidence: 99%
“…Recent data also indicate the involvement of GII␤ in the maturation of the glucosidase II heterodimer. While coexpression of the alpha and beta subunits increases total glucosidase II activity, expression of GII␣ alone results in an insoluble and inactive aggregate (65,85). However, once GII␣ is fully folded, the beta subunit is no longer necessary for activity (86).…”
mentioning
confidence: 99%